Innovated Building Material's Interactions with Structural Form in Architectural Projects - Mozaikci, Begüm (Eastern Mediterranean University (EMU), 2009)
ABSTRACT: Interpretation of building materials into architectural form, is gaining greater interest and attention due to the conservation of architectural heritage. This study highlight, the influences of technological developments of building materials and their interactions with structural form in architectural design projects. Architectural form and decisions can potentially effects by introduced new materials and this study focus on the interaction of new material and structural form, moreover it is more focus on contemporary architectural forms including construction methods and technology used. With the innovation of new material and improvement of the existing materials properties this thesis aimed to argue about what is happening to the building material and structural forms relationship in the context of architectural design projects. The practical constraints of the design projects in the process of realizing them which is building materials will be discuss in the whole research. This study prepared to draw a attention of the architect’s and architecture student`s to the influences of technology and building materials on architectural design projects. This will be done by documentary researches related to the Technology, Building Material, Structural Form, Form and Structure in architecture field and deep investigation of six selected materials with respect to technology factors in their existing time through the years will be discuss to show bulding material and structural from relation modification respect to time. Keywords: Building Materials, Structural Form, Structure, Form, Technology and Architectural Design. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZET: Mimari mirasın korunması adına mimari form üzerinden yapı malzemeleri ile ilgili yapılan yorumlar büyük ilgi ve önem kazanmaktadır. Bu çalısmanın amacı yapı malzemelerinin teknolojik gelisme ile gelen etkilerinin stürüktürel formla iliskisinin mimari tasarım projeleri çerçevesinde incelemektir. Mimari form ve kararlar büyük bir ölçüde yeni tanıtılan malzemelerden etkilenmektedir. Bu çalısmanın odak noktası yeni malzemeler ve stürüktürel form ve bunların birbiriyle olan iliskileridir. Bununda ötesinde çağdas mimari yapı malzemeleri, formları, insaat teknikleri, kullanılan teknoloji ve bulunulan zaman incelenmektedir. Yeni malzemelerin gelisimiyle ve var olan malzemelerin gelistirilmesiyle, mimari tasarım projeleri çerçevesinde yapı malzemeleri ve stürüktürel form iliskisine ne olduğu tartısılacaktır. Tasarım projelerin gerçeğe dönüsmesinde pratik (Kullanılabilirlik) kısıtlayıcı olarak yapı malzemeleri tartısılacaktır. Bu çalısma mimarların ve mimarlık öğrencilerinin teknolojiye ve yapi malzemelerinn mimari projelere olan etkisine dikkat çekmek için düzenlenecektir. Bunlar mimarlık alanındaki teknoloji, yapı malzemeleri, stürüktürel form, form ve stürüktür ile ilgili kaynak taramaları ve seçilen altı malzeme ile ilgili tecknolojik gelismelerini zaman içerisinde göz önüne alınarak yapılan detaylı arastırmalarlar ile gerçeklestirilecektir. Anahtar Kelimeler: Yapı Malzemeleri, Stürüktürel biçim, Stürüktür, Form (Biçim), Teknoloji ve Mimari Tasarımlar.
Master of Science in Architecture. Thesis(M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2009. Supervisor: Assoc. Prof. Dr. Munther Moh`d.
Keywords: Architecture; Architecture - Form; Building Materials - Structural Form - Technology and Architectural Design